2013
DOI: 10.1155/2013/925702
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Memantine, Donepezil, or Their Association in Moderate‐Severe Alzheimer’s Disease: A Review of Clinical Trials

Abstract: Background. Acetylcholinesterase (AChE)/cholinesterase (ChE) inhibitors (Is) and memantine are licensed for symptomatic treatment of mild-moderate and moderate-severe forms of Alzheimer's disease (AD), respectively. High doses of the AChE-I donepezil were licensed in the USA for moderate-severe AD, and the association AChE/ChE-Is plus memantine was proposed for AD at this stage. Objectives. This paper has reviewed evidence from clinical trials of the effectiveness of memantine, donepezil, or the two drugs in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 39 publications
1
31
0
4
Order By: Relevance
“…Previous studies have also indicated that when the course of the disease progresses to moderate or severe levels, combination treatments are more effective than single treatment for delaying the degradation of cognitive functions [12,14,[15][16][17][18][19][20][21][22]. Further, we have reported that memantine administered to patients with moderate to severe AD may inhibit the reduction of cerebral blood flow in the prefrontal area, improve global clinical symptoms, cognitive function and BPSD, and lighten the burden of care placed on caretakers [23].…”
Section: Research Rei Wakementioning
confidence: 84%
“…Previous studies have also indicated that when the course of the disease progresses to moderate or severe levels, combination treatments are more effective than single treatment for delaying the degradation of cognitive functions [12,14,[15][16][17][18][19][20][21][22]. Further, we have reported that memantine administered to patients with moderate to severe AD may inhibit the reduction of cerebral blood flow in the prefrontal area, improve global clinical symptoms, cognitive function and BPSD, and lighten the burden of care placed on caretakers [23].…”
Section: Research Rei Wakementioning
confidence: 84%
“…More recently, a combination drug using memantine and donepezil (Namzaric) was approved by the FDA for moderate to severe Alzheimer's. While the drug combination appeared to be well tolerated when given for several months to Alzheimer's patients, no significant benefits were found when the drug combination was compared to either therapy alone [4].…”
Section: Treating Alzheimer'smentioning
confidence: 85%
“…By inhibition of AChE/ChE, the enzymes degrading acetylcholine in the synaptic cleft, they enhance the cholinergic transmission and slow down of the acetylcholine (ACh) catabolism which makes acetylcholine more concentrated [4].…”
Section: Introductionmentioning
confidence: 99%